1983
DOI: 10.1021/bi00277a046
|View full text |Cite
|
Sign up to set email alerts
|

pH dependence of the redox reaction of azurin with cytochrome c551: role of His-35 of azurin in electron transfer

Abstract: A fluorescence quenching experiment confirms that in the redox reaction between cytochrome c-551 and azurin, protein complexing is negligible. Azurin-pH indicator T-jump experiments show that Pseudomonas aeruginosa (Ps.) azurin exhibits a slow time constant, tau, in its return to pH equilibrium but Alcaligenes faecalis (Alc.) azurin does not. The decrease of l/tau with increasing pH shows that the rate-determining process is a slow transformation of the imidazolium form of histidine-35 from a conformation wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 21 publications
5
26
1
Order By: Relevance
“…65 The population of the N ε tautomer by the deprotonated His-35 is also clearly evident from the available structural information at a pH value of 9.0 12 (see Figure 1b). The pK 1/2 values of His-35 and His-83 are consistent with direct NMR measurements 14,64À66 and indirect fits to kinetic 20,56 and voltammetry data. 21,58 Even pK 1/2 values that are measured directly with NMR are afflicted with a typical methodological uncertainty of ≈1 pH unit.…”
Section: Resultssupporting
confidence: 83%
“…65 The population of the N ε tautomer by the deprotonated His-35 is also clearly evident from the available structural information at a pH value of 9.0 12 (see Figure 1b). The pK 1/2 values of His-35 and His-83 are consistent with direct NMR measurements 14,64À66 and indirect fits to kinetic 20,56 and voltammetry data. 21,58 Even pK 1/2 values that are measured directly with NMR are afflicted with a typical methodological uncertainty of ≈1 pH unit.…”
Section: Resultssupporting
confidence: 83%
“…We emphasize that, although several NMR studies have shown that His-35 ionization causes structural changes in the vicinity of the Cu atom and that "high-pH" and "low-pH" conformations of azurin can be identified (3,27,28), there is no direct evidence that shows that electron exchange kinetics of these distinct conformations are sufficiently different to warrant identifying them with a redox "active" or "inactive" form. On the contrary, our data and the data of others (6,23,26) indicate that electron exchange kinetics of azurin is relatively pH independent. This leads to the conclusion that the complex decay seen in T-jump experiments may arise, as previously suggested (3), from the pKa of His-35 being significantly different in the oxidized and reduced proteins.…”
Section: Rate Measurementscontrasting
confidence: 77%
“…It was suggested that through structural perturbations induced near the copper center, "the electron exchange efficiency between azurin and the Cyt c551 may be affected by the ionization of this histidine and/or that the PKa of this residue is different in the oxidized and reduced azurins, resulting in complex equilibria and decay kinetics in the reported temperature-jump experiments, which were carried out at neutral pH" (3). All subsequent experiments concerned with this question (6,12,(22)(23)(24)(25) indicate that the protonation reaction of the His-35 residue is indeed the source of the complex decay kinetics observed in T-jump studies of electron exchange between azurin and Cyt c551. However, any model in which the electron exchange rate between azurin and Cyt c is proposed to be significantly altered by the ionization state of His-35 is inconsistent with the fact that the electron transfer rate between Cyt c551 and azurin is independent of pH in the range 5.0-9.0 (6, 23, 26) and with our current results, which show that the self-exchange rate constant is not affected by His-35 ionization.…”
Section: Rate Measurementsmentioning
confidence: 99%
See 2 more Smart Citations